Spacecraft radio signal polarization calibration - Jensen, Elizabeth A.; Kepley, Amanda; Wexler, David; Kobelski, Adam; Kooi, Jason E.; Valliani, Aahil; Cho, Aidan; Heisey-Grove, Egan; Kumari, Anshu; Fung, Shing F. (Frontiers in Astronomy and Space Sciences, 2025)
IntroductionThe only reliable method to remotely obtain magnetic field information across large swaths of interplanetary/interstellar plasma is with the measurement of Faraday rotation of polarized radio signals.MethodsFocusing on the high frequency regime of magnetized plasmas, this paper discusses the most difficult first step toward obtaining these measurements. Transitioning from raw voltage samples to plane of polarization measurements requires both simulated signal tests and qualitative inspections of the behavior of the resulting measurements.ResultsTo demonstrate how this calibration approach works, we show examples collected from the STEREO A and B spacecraft and the Mars Reconnaissance Orbiter spacecraft.DiscussionWhile astronomical radio sources have their own challenges to data processing, we show that spacecraft data have their own unique characteristics that can benefit and hinder the data processing.